Computer-Aided Evaluation of Ethanol Production from a Continuous Operating Mode using Simulink (2021)
Fossil fuels have become a great energy source worldwide. However, its prolonged use has caused severe environmental pollution problems. Biofuels generated from biomass as a product of microbial biotechnology emerge as an alternative to the use of compounds derived from oil. Therefore, their production results in complex experiments and source investment. That is why engineering studies implementation using mathematical models and simulation techniques should be specified in bioprocesses. The latter focused on optimizing the process parameters, maximizing productivity, generating greater profitability, and reducing cost. This research aimed at the computer-assisted evaluation of obtaining bioethanol from Saccharomyces cerevisiae to determine the most critical factors in the production process using a continuous mode. It was determined that the feed rate significantly influences the bioethanol volumetric productivity.